TSV by 355 UV laser for 4G component packaging with micro-electroforming. (November 2017) - Pan, C.T.; Chen, Y.C.; Wang, S.Y.; Cheng, Y.T.; Yen, C.K.; Lin, Y.L.; Shih, W.C.
Abstract: Nickel micro-electroforming was integrated with 355-nm wavelength ultraviolet laser process to fabricate the through silicon via (TSV) for 4G communication device packaging. This technology was applied to package the high-frequency solidly mounted resonator (SMR). Different parameters including laser power, focus length, frequency, and termination diameter were explored to characterize the quality of TSV for laser drilling. The thickness of silicon sample of 550 μm was drilled. The diameter of the silicon by laser drilling was 100–110 μm, where the taper was about 1.6° and the aspect ratio was about 5. The relationship between micro-electroforming deposition thickness and time were obtained. The deposition thickness was carried out by various current densities under 0.5 Amps per square decimeter (ASD), 1 ASD, 2 ASD, and 4 ASD, respectively, to analyze the electroplating quality. In addition, nanoindenter, energy dispersive spectrometer (EDS), and X-ray diffraction (XRD) were used to analyze the material characteristics of micro-electroforming samples. Laser drilling and micro-electroforming were integrated to package the high-frequency SMR. The result shows that the S11 parameter was − 3.5 dB under the frequency of 2.5 GHz. This TSV with micro-electroforming process shows potential use for 4G packaging application. Highlights: Micro-electroforming is used to fill up the conductive via to make connections between chips. UV laser processing combined micro-electroforming process was applied to obtain the minimum package area. Laser drilling and micro-electroforming were integrated to package the high-frequency SMR. Silicon chip with vias was sealed using photoresist on glass wafer with ITO thin film atop to electroform.